Estudo da derivação duodenojejunal sobre a estrutura das fibras musculares e junções neuromusculares do músculo diafragma de ratos obesos induzidos por dieta de cafeteria - Ulsenheimer, Bruna Hart (2014)
Concerning obesity, the diaphragm dynamics can be impaired due to the excess of fat deposited in thorax and abdomen, leading to changes in respiratory function. A technique of bariatric surgery known as duodenal-jejunal bypasses (DJB) has been investigated as a treatment strategy in obesity and its comorbidities. However, the effects of this procedure on skeletal muscles have not yet been observed. The present study aimed at investigating the DJB effects on the neuromuscular junctions (NMJs) and muscle fibers of diaphragm of obese rats induced by cafeteria diet. Male Wistar rats were divided into two groups: a control group (CTL) that received a standard diet and water, and Western Diet group (WD) that received a cafeteria diet and soft drink for 10 weeks. After this period, WD group was distributed into two groups: WD sham-operated rats (WD SHAM); and WD DJB-operated rats (WD DJB). Following surgery, both the WD groups continued to receive the cafeteria diet. After eight weeks, the animals were euthanized and samples of diaphragm muscle were collected to analyze its fibers, quantify its collagen and evaluate NMJs morphometric. WD SHAM rats displayed an increase in body weight, the Lee index and retroperitoneal and peri-epididymal fat pads compared to the CTL group and DJB surgery did not alter these parameters. The muscle fiber structure and NMJs were similar in the WD SHAM and CTL groups. However, the WD SHAM group showed alterations in the fiber ultrastructure, such as loosely arranged myofibrils and Z line disorganization in the diaphragm. In addition, WD SHAM animals presented a considerable amount of lipid droplets and a reduction in the percentage of collagen in diaphragm muscle compared to the CTL group. DJB did not affect the structure or ultrastructure of the muscle fibers or the NMJs in the diaphragm of the WD DJB animals. Two months after the procedure, DJB did not improve the alterations observed in the diaphragm of WD obese-rats.